Recommendations for the diagnosis and management of Fabry disease in pediatric patients: a document from the Rare Diseases Committee of the Brazilian Society of Nephrology (Comdora-SBN) - Vaisbich, Maria Helena; Andrade, Luís Gustavo Modelli De [UNESP]; Silva, Cassiano Augusto Braga; Barreto, Fellype De Carvalho (Sociedade Brasileira de Nefrologia, 2022)
Fabry disease (FD) is a genetic disease, with X-chromosome linked inheritance, due to variants in the GLA gene that encodes the α-galactosidase A (α-GAL) enzyme. The purpose of the present study was to create a consensus aiming to standardize the recommendations regarding the renal involvement of FD with guidelines on the diagnosis, screening, and treatment of pediatric patients. This consensus is an initiative of the Rare Diseases Committee (Comdora) of the Brazilian Society of Nephrology (SBN). Randomized controlled clinical studies and studies with real-life data added to the authors' experience were considered for this review. The result of this consensus was to help manage patient and physician expectations regarding treatment outcomes. Thus, this consensus document recommends the investigation of the pediatric family members of an index case, as well as cases with suggestive clinical signs. From the diagnosis, assess all possible FD impairments and grade through scales. From an extensive review of the literature including pediatric protocols and particularly evaluating pediatric cases from general studies, it can be concluded that the benefits of early treatment are great, especially in terms of neuropathic pain and renal impairment parameters and outweigh the possible adverse effects that were mainly manifested by infusion reactions.
Keywords: Fabry Disease; Consensus; Rare Diseases